Implementation of ETLE in Improving Traffic Law Compliance in Indonesia - Candra, Panji Ali; Sudiro, Amad; Gunadi, Ariawan (Journal of Posthumanism, 2025)
This study aims to analyze the effectiveness of the implementation of the Electronic Traffic Law Enforcement (ETLE) system in traffic law enforcement in Indonesia. The problems raised include the high level of traffic violations, the ineffectiveness of manual law enforcement, and the potential for deviations in the application of administrative sanctions. This study uses a descriptive method with a qualitative approach, utilizing primary data through interviews and secondary data in the form of statistical documentation of traffic violations in the jurisdiction of the Polda Metro Jaya. The results of the study indicate that the ETLE system is able to increase transparency and efficiency of traffic law enforcement by minimizing direct interaction between the police and violators, thereby reducing the potential for deviations such as bribery. In addition, ETLE has proven effective in automatically detecting violations and providing a deterrent effect on violators through the imposition of integrated sanctions. However, challenges still exist, such as limited ETLE camera coverage, a lack of socialization with the community, and technical constraints in operating the system. The ETLE system is an innovation that supports the modernization of traffic law enforcement in Indonesia. To increase its effectiveness, it is necessary to strengthen technological infrastructure, expand the coverage area, and educate the community regarding the importance of traffic compliance.